Odpowiedź :
Odpowiedź:
Poziom C
g) 5 - 2 • x = 9 - 6 • x
-2 • x + 6 • x = 9 - 5
4 • x = 4 /: 4
x = 1
h) -6 + 4 • x = 5 • x + 4
4 • x - 5 • x = 4 + 6
-x = 10 /: (-1)
x = -10
Poziom D
a) 5 • x - 3 + 2 • x = 4 • x + 9
5 • x + 2 • x - 4 • x = 9 + 3
3 • x = 12 /: 3
x = 4
c) 2 + 4 • x - 1 + 2 • x = -8 + 4 • x - 7
4 • x + 2 • x - 4 • x = -8 - 7 - 2 + 1
2 • x = -16 /: 2
x = -8
Pozdrawiam.
g. 5 - 2x = 9 - 6x
-2x + 6x = 9 - 5
4x = 4 | :4
x = 1
h. -6 + 4x = 5x +4
4x - 5x = 4 + 6
-x = 10 | *-1
x = -10
a. 5x - 3 + 2x = 4x + 9
7x - 4x = 9 + 3
3x = 12 |:3
x = 4
c. 2 + 4x - 1 + 2x = - 8 + 4x - 7
6x + 1 = 4x - 15
6x - 4x = - 15 - 1
2x = - 16 | :2
x = -8